Gonadotropine Releasing Hormone (GnRH) Receptor Profile from Cow’s Hypothalamus - Irma Dian Nurani; Claude Mona Airin; Pudji Astuti; Khrisdiana Putri; Bambang Sutrisno (Jurnal Sain Veteriner, 2020)
Gonadotropine Releasing Hormone (GnRH) is one of the recommended hormones to overcome ovulation problems and it can increase pregnancy rate so that it is used in government programs to increase cattle population in Indonesia, although the results are not yet optimal. The purpose of this study is to compare the composition of bovine GnRH receptor nucleotides with the GenBank reference so that the level of genetic diversity of bovine receptors in Indonesia is known. PCR product sequencing using Promoter F and Exon 1 R primers were further aligned with the reference sequences of Bos Taurus GnRHR mRNA GenBank using the MEGA X program. The results of the analysis found the presence of Single Nucleotide Polymorphism (SNP) in the coding region  of 1st cow  position 38(A> T), 261(C > T), 342(C >T), 411(C >T) and 495(C > T) and 2nd cow positions 261(C >T). Changes in amino acids were also detected in 1st cow position 13 (H> L). The presence of SNP was found to indicate genomic variation between individuals at cattle receptors in Indonesia.